Comparison of physical and mechanical properties of river sand concrete with quarry dust concrete - Opara Hyginus E.; Eziefula Uchechi G.; Eziefula Bennett I. (Selected Scientific Papers: Journal of Civil Engineering, 2018)
This study compared the physical and mechanical properties of river sand concrete with quarry dust concrete. The constituent materials were batched by weight. The water-cement ratio and mix ratio selected for the experimental investigation were 0.55 and 1:2:4, respectively. The specimens were cured for 7, 14, 21 and 28 days. Slump, density and compressive strength tests were carried out. The results showed that river sand concrete had greater density and compressive strength than quarry dust concrete for all curing ages. At 28 days of curing, river sand concrete exceeded the target compressive strength by 36%, whereas quarry dust concrete was less than the target compressive strength by 12%. Both river sand concrete and quarry dust concrete for the selected water/cement ratio and mix ratio are suitable for non-structural applications and lightly-loaded members where high strength is not a prerequisite.